"Access to technology is the major challenge": Teacher perspectives on barriers to DGBL in K-12 classrooms. (May 2021) - Hébert, Cristyne; Jenson, Jennifer; Terzopoulos, Tatyana
In this article, we report on a study of 32 teachers and their implementation of a digital game designed to support the human and physical geography curriculum in grades 7 and 8 in the province of Ontario, Canada. The purpose of the paper is to analyze and robustly represent the experiences of teachers who participated in the study, most of whom had never before constructed an integrated learning experience utilizing a digital game with one of their classes. By centering teacher voices, which often do not appear in research on digital game-based learning (DGBL), we hope to provide insight into some of the real challenges of incorporating digital games into classrooms.